Indigenous Knowledge of Javanese in the Radya Pustaka Museum Collections - Nurislaminingsih, Rizki; Heriyanto, Heriyanto; Bakry, Gema Nusantara; Prasetyawan, Yanuar Yoga (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2024)
Radya Pustaka Museum is a museum that represents Javanese culture. The collections in the museum are proof of the indigenous knowledge of the people in making cultural products. This research aims to identify Javanese indigenous knowledge based on the Radya Pustaka Museum collections. Therefore, qualitative research was used with a museum study approach to identify types of indigenous knowledge based on various museum collections. The results of the research show that indigenous knowledge represented in the collection at the Radya Pustaka Museum is how to make Javanese men's headgear (blangkon), turn tree bark into paper (daluang), use palm leaves (lontar) as a writing medium, cast copper for writing media, turn metal into various weapons, making puppets (from animal skin and wood), creating traditional orchestral musical instruments (gamelan), mastering Javanese astrology (pawukon), turning a hill into a burial complex, assembling a traditional cruise ship, understanding the health benefits from coconut water, and making natural paint, natural dyes, and glue. This research found that the indigenous knowledge behind gamelan is not only about how to make musical instruments and how to create notes, but there is also knowledge about mental health. Music produced from gamelan can calm the mind, facilitate concentration, and increase enthusiasm for living life. Another finding is that there is ethnomathematics implicit in the Imogiri burial complex. The results of this research can be a reference source for further research on local knowledge management in information institutions, especially museums, so that employees can service the knowledge behind the collections.